2022
DOI: 10.3390/molecules27134028
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Resveratrol against Hexavalent Chromium-Induced Genotoxic Damage in Hsd:ICR Male Mice

Abstract: The aim of this study is to examine the ability of resveratrol to counteract hexavalent chromium [Cr(VI)]-induced genetic damage, as well as the possible pathways associated with this protection. Hsd:ICR male mice are divided into groups of the following five individuals each: (a) control 1, distilled water; (b) control 2, ethanol 30%; (c) resveratrol, 50 mg/kg by gavage; (d) CrO3, 20 mg/kg intraperitoneally; (e) resveratrol + CrO3, resveratrol administered 4 h prior to CrO3. The assessment is performed on per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…A significant increase in MN frequencies (12-60 h after CrO 3 treatment) demonstrated Cr(VI)-induced genotoxicity. This is consistent with previous findings evaluating Cr(VI)-induced genotoxicity (10,11), and particularly by CrO 3 (12,13). The underlying genotoxic mechanism of the action of Cr(VI) has been linked to the intracellular reduction of Cr(VI) to Cr(III).…”
Section: Discussionsupporting
confidence: 92%
“…A significant increase in MN frequencies (12-60 h after CrO 3 treatment) demonstrated Cr(VI)-induced genotoxicity. This is consistent with previous findings evaluating Cr(VI)-induced genotoxicity (10,11), and particularly by CrO 3 (12,13). The underlying genotoxic mechanism of the action of Cr(VI) has been linked to the intracellular reduction of Cr(VI) to Cr(III).…”
Section: Discussionsupporting
confidence: 92%
“…RES reduces Chromium-induced MN frequency and can repair cells. This is due to the polyphenol content and antioxidant properties of RES (Nicolás-Méndez et al, 2022). It was concluded that the dose of RES-tempeh with a dose of 10 mg/kg BW can increase the number of osteocytes.…”
Section: Discussionmentioning
confidence: 98%